An axiomatic foundation of conditional logit - Yves Breitmoser (Economic Theory, 2020)
This paper considers a decision maker choosing from a set of options when options have multiple real-valued attributes. Assuming DM chooses all options with positive probability, four invariance assumptions are necessary and sufficient for choice probabilities to take McFadden's conditional logit form: independence of irrelevant alternatives, translation invariance, presentation independence and context independence. Variations on these assumptions yield generalized logit and contextual logit models. This shows that even specific logit models have behavioral foundations in simple invariance assumptions involving observables only, which therefore are directly testable.
Keywords: D01; C13; 330; Conditional logit; Axiomatic foundation